Deguelin suppresses non-small cell lung cancer by inhibiting EGFR signaling and promoting GSK3β/FBW7-mediated Mcl-1 destabilization - Gao, Feng (Cell Death Dis, 2020)
Activating mutations of epidermal growth factor receptor (EGFR) play crucial roles in the oncogenesis of human non-small cell lung cancer (NSCLC). By screening 79 commercially available natural products, we found that the natural compound deguelin exhibited a profound anti-tumor effect on NSCLC via directly down-regulating of EGFR-signaling pathway. Deguelin potently inhibited in vitro EGFR kinase activity of wild type (WT), exon 19 deletion, and L858R/T790M-mutated EGFR. The in silico docking study indicated that deguelin was docked into the ATP-binding pocket of EGFRs. By suppression of EGFR signaling, deguelin inhibited anchorage-dependent, and independent growth of NSCLC cell lines, and significantly delayed tumorigenesis in vivo. Further study showed that deguelin inhibited EGFR and downstream kinase Akt, which resulted in the activation of GSK3β and eventually enhanced Mcl-1 phosphorylation at S159. Moreover, deguelin promoted the interaction between Mcl-1 and E3 ligase SCF(FBW7), which enhanced FBW7-mediated Mcl-1 ubiquitination and degradation. Additionally, phosphorylation of Mcl-1 by GSK3β is a prerequisite for FBW7-mediated Mcl-1 destruction. Depletion or pharmacological inactivation of GSK3β compromised deguelin-induced Mcl-1 ubiquitination and reduction. Taken together, our data indicate that enhancement of ubiquitination-dependent Mcl-1 turnover might be a promising approach for cancer treatment.